2021
DOI: 10.3390/cancers13153866
|View full text |Cite
|
Sign up to set email alerts
|

Age and Cohort Trends of Malignant Melanoma in the United States

Abstract: The incidence of malignant melanoma in the United States is increasing, possibly due to changes in ultraviolet radiation (UVR) exposure due to lifestyle or increased awareness and diagnosis of melanoma. To determine if more recent birth cohorts experience higher rates of melanoma as they age, we examined age and birth cohort trends in the United States stratified by anatomic site and cancer type (in situ vs. malignant) of the melanoma diagnosed from 1975–2017. Poisson regression of cutaneous melanoma cases per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Using the SEER registry, Lashway et al (2021) found that CM incidence increased with age between 1975 and 2017. After adjusting for age and stratifying groups into 5-year birth cohorts, these researchers discovered significantly greater melanoma incidence at older ages [ 15 ]. Paulson et al (2019) further this age-based dichotomy when reporting that CM incidence decreased in populations under 40 years old between 2006 and 2015 but increased in people 40 years old and over during the same time [ 16 ].…”
Section: Putative Reasons For Increased Incidence Of Melanomamentioning
confidence: 99%
See 2 more Smart Citations
“…Using the SEER registry, Lashway et al (2021) found that CM incidence increased with age between 1975 and 2017. After adjusting for age and stratifying groups into 5-year birth cohorts, these researchers discovered significantly greater melanoma incidence at older ages [ 15 ]. Paulson et al (2019) further this age-based dichotomy when reporting that CM incidence decreased in populations under 40 years old between 2006 and 2015 but increased in people 40 years old and over during the same time [ 16 ].…”
Section: Putative Reasons For Increased Incidence Of Melanomamentioning
confidence: 99%
“…The steep increase in biopsy and diagnosis rates of thinner melanomas, in particular, has augmented the total number of tumor cases identified [ 4 , 9 , 18 , 19 , 20 ]. Critical contributors to these observed trends include increased skin cancer awareness by patients and providers and efforts targeting primary and secondary prevention at the local and national levels [ 15 , 18 , 20 ]. Before professional associations like the American Academy of Dermatology endorsed melanoma screenings, CM diagnosis generally revolved around the presence of distinguishable macroscopic findings like size and ulceration; as a result, the disease was often identified during its later stages [ 15 ].…”
Section: Increased Skin Cancer Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear understanding of the prognostic factors for malignant cutaneous melanoma is becoming increasingly paramount as its incidence continues to rise in the United States (1). Strong evidence has demonstrated that greater Breslow thickness and ulceration are correlated with melanoma-specific mortality (MSM), resulting in their inclusion in the staging system.…”
Section: Introductionmentioning
confidence: 99%
“…Solar ultraviolet radiation (UVR) exposure remains the major environmental risk factor for developing CMM. Despite public health initiatives that have promoted sun protection, the incidence of CMM continues to increase, with much of the increased incidence driven by thin CMM [ 1 , 2 ]. According to recent predictions from the American Cancer Society, an estimated 106,110 new cases of invasive melanoma and 101,280 cases of melanoma in situ will be diagnosed in the US in 2021 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%